The emotion ∼ intellect dialectic in an EFL teacher's development of a research identity: A sociocultural perspective. (December 2022) - Zhang, Yanhua; Lantolf, James P.; Meng, Yaru
Abstract: Language teacher identity development often entails the negotiation of the tensions that arise between how individuals interpret their identity as educators and the demands of the educational system in which they work. How these tensions are confronted and resolved (or not) is not well understood. To improve understanding of this under-researched topic, this study relies on a core theoretical concept of Vygotskian sociocultural theory, perezhivanie (the unity of emotion and intellect) that individuals experience as they confront specific circumstances that arise in the social environment in which they live. Specifically, we used the concept to analyze the narrative of a university professor who experienced negative and positive emotions resulting in an identity crisis as he confronted and overcame the demands of a postsecondary educational system as it shifted from a teaching to a research focus. The study reveals how the interaction between teacher-researcher and the social environment first challenged his identity as a teacher and then through an intense emotional structure enabled him to create an identity as a researcher. A discussion of the implications of our analysis for post-secondary educators confronting similar circumstances are considered.